Employing literary news in the issue of choosing words among Arabs - Othman, Heam Abdul Qadir; Hadi, Salah Kazem (Al-Adab Journal, 2021)
Our literary heritage is full of precious treasures and jewels as long as critics have been discovering, refining and benefiting from them, and the news is one of the important aspects of literature in general and an active document in literature criticism, as literary criticism has grown naturally with the growth of arts of literary expression over the tongues of the people of the statement from the stage of speech to the codification stage In the pre-Islamic era, it began based on taste and common sense that are influenced by what one hears of poetic creativity and interacts with it with approval, approval and differentiation.Attitudes and critical judgments are formed in the aftermath. The news included in his various literary speeches all the arts of saying and keeping us those opinions and judgments, so the critics took care of collecting it, writing it down, then classifying it and classifying it in a way that serves their demands and issues on the one hand, and the reader enjoys and facilitates him the way to read and benefit on the other hand, especially since gathering these news in Volumes and books were an imperative, and had it not been for the scholars to restrict their thoughts and opinions and preserve the traces of those who preceded them, the first science was null and late. Accordingly, Arab critics used literary news in the field of their theoretical and applied studies, addressed issues and critical issues with it and built their topics by telling the news, and they relied on it as a document and a reference window, witness and historical and scientific argument and for this we realize experience and certain that the news has a clear impact in framing the critical efforts of our brilliant scholars and directing research In the field of literary criticism, positive guidance is given; Because the value of the judgment that the critic releases stems from his use of the news as a tool for supporting these judgments and a way to convince the recipient of their content .